2020
DOI: 10.1038/s41419-020-02908-w
|View full text |Cite
|
Sign up to set email alerts
|

1,25-dihydroxyvitamin D3 signaling-induced decreases in IRX4 inhibits NANOG-mediated cancer stem-like properties and gefitinib resistance in NSCLC cells

Abstract: Recent studies have demonstrated that acquisition of cancer stem-like properties plays an essential role in promoting epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) resistance in non-small cell lung cancer (NSCLC); however, how to regulate cancer stem-like properties and EGFR-TKI resistance is largely unclear. In this study, we discovered that increased iroquois-class homeodomain protein 4 (IRX4) was related to gefitinib resistance in NSCLC cells. Knockdown of IRX4 inhibited cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Similarly, previous studies have shown that vitamin D derivatives exert synergistic effects when used in combination with other oncological drugs [18][19][20][21]. In particular, it has been demonstrated that the combination of calcitriol or its analogs with gefitinib, a synthetic RTKI, enhances global anticancer activity by inhibiting tumor growth and inducing apoptosis, and in cancer patients it does not result in serious undesirable side effects [17,20,43,44]. To the best of our knowledge, this is the first study addressing the antineoplastic effects of dovitinib in combination with calcitriol.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, previous studies have shown that vitamin D derivatives exert synergistic effects when used in combination with other oncological drugs [18][19][20][21]. In particular, it has been demonstrated that the combination of calcitriol or its analogs with gefitinib, a synthetic RTKI, enhances global anticancer activity by inhibiting tumor growth and inducing apoptosis, and in cancer patients it does not result in serious undesirable side effects [17,20,43,44]. To the best of our knowledge, this is the first study addressing the antineoplastic effects of dovitinib in combination with calcitriol.…”
Section: Discussionmentioning
confidence: 85%
“…Calcitriol, the vitamin D most active metabolite, exert potent antineoplastic activity by modulating diverse signaling networks involved in inhibition of cell proliferation, anti-inflammatory effects, acquisition of a more differentiated phenotype and induction of apoptosis [16]. Moreover, calcitriol has been shown to increase the sensitivity of tumor cells to various chemotherapeutic agents [17][18][19][20][21], with the added benefit of being a natural compound derived from dietary sources or by sun exposure. Notably, low vitamin D serum levels have been shown to correlate with increased risk of certain neoplasms, including breast cancer [22].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-tumoral cellular heterogeneity is a major hallmark of lung cancers. Several molecules, such as CD133 ( Chen et al, 2008 ; Jia et al, 2020 ), have been suggested as markers of the aggressive cancer cell population with stem cell features. Importantly, although PORCN+ cells have a critical role in LUAD progression in a mouse model ( Tammela et al, 2017 ), no attempt has been made to isolate these Wnt-producing niche cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dichloroacetate PDHK inhibitor Induction of Acetyl-CoA formation [26] Atorvastatin CAV-1/GLUT-3 inhibitor Inhibition of glucose uptake and cholesterol synthesis [30] PF-429242 SREBP1 inhibitor Inhibition of lipid synthesis [31] Orlistat FASN inhibitor Inhibition of EGFR palmitoylation [32] Epalrestat AKR1B1 inhibitor Inhibition of GSH synthesis [33] PiperlongumineAuranofin ROS inducing agent Induction of oxidative stress [34] Buthionine sulfoximine GSH synthesis inhibitor Inhibition of GSH synthesis [34] 1,25D VDR agonist Inhibition of stemness phenotype [35] AZ12756122 FASN inhibitor Inhibition of stemness phenotype [36] Abbreviations: PDHK, pyruvate dehydrogenase kinase; Acetyl-CoA, acetyl coenzyme A; CAV-1, caveolin-1; GLUT-3, glucose transporter-3; FASN, fatty acid synthase; EGFR, epidermal growth factor receptor; SREBP1, sterol regulatory-element-binding protein 1; AKR1B1, aldo-keto reductase family 1 member B1; GSH, glutathione; ROS, reactive oxygen species; 1,25D, 1,25-dihydroxyvitamin D3; VDR, vitamin D receptor.…”
Section: Mechanism Of Action Downstream Effect Referencementioning
confidence: 99%